Discovering anaemia at child health clinics. Issue 8 (August 1990) - Marder, E; Nicoll, A; Polnay, L; Shulman, C E
Abstract : Children at three inner city child health clinics were offered haemoglobin estimation by fingerprick blood test when attending for immunisation against measles. Of the 98 immunised, 92 (94%) participated in the study, together with 58 other children. Anaemia (haemoglobin concentration less than 110 g/l) was found in 33 of 130 overall (25%), and in 17 of 44 Asian children (39%). The method of testing was acceptable to parents and staff.